2015
DOI: 10.1159/000398791
|View full text |Cite
|
Sign up to set email alerts
|

Role of Microglia in Autism: Recent Advances

Abstract: The neurobiological basis for autism remains poorly understood. However, the neuroinflammation processes play an important role in the induction of autistic behavioral changes. Microglial cells can exhibit widely differing functions during brain development, including synaptogenesis and stem cell proliferation, in addition to playing a role in the innate immunity. Mounting evidence indicates that microglial activation or dysfunction can profoundly affect neural development, resulting in neurodevelopmental diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 70 publications
(78 reference statements)
2
85
0
1
Order By: Relevance
“…Indeed, recent neuropathological studies in human post-mortem brains have revealed strong microglial activation in neurodevelopmental disorders, such as schizophrenia (de Baumont et al, 2015; Sekar et al, 2016), and ASD (Voineagu et al, 2011; Gupta et al, 2014; Takano, 2015). …”
Section: Microglial Perturbations During Brain Developmentmentioning
confidence: 99%
“…Indeed, recent neuropathological studies in human post-mortem brains have revealed strong microglial activation in neurodevelopmental disorders, such as schizophrenia (de Baumont et al, 2015; Sekar et al, 2016), and ASD (Voineagu et al, 2011; Gupta et al, 2014; Takano, 2015). …”
Section: Microglial Perturbations During Brain Developmentmentioning
confidence: 99%
“…Given that immune-system-related genes are not highly prevalent among the genetic candidates for ASD risk, alterations in the expression and methylation of immune genes in ASD may occur in reaction to abnormal neurodevelopment and/or in response to environmental factors. Microglia are observed to be activated in the ASD brain 88 ; however, differences in microglial-specific methylation patterns in ASD are currently unknown.…”
Section: Dna Methylation In Asdmentioning
confidence: 99%
“…The presence of activated microglia has been reported in the dorsolateral prefrontal cortex of autistic patients [30]. Moreover, Positron Emission Tomography (PET) imaging studies have revealed an activation of microglia in other brain regions [31, 32]. Postmortem studies of individuals with ASD have also shown activation of microglia, as well as an increase in density [30, 33, 34].…”
Section: Evidence Of Neuroinflammatory Processes In Autismmentioning
confidence: 99%